ALGORITHM OF FORMATION OF RISK GROUPS FOR BIRTH OF CHILDREN WITH NEURAL TUBE DEFECTS AMONG REPRODUCTIVE AGE WOMEN AND DIFFERENTIATED APPROACH TO PREVENTION OF THE SPINAL DISRAPHIA - N. Kotova; V. Maychuk (Bukovynian State Medical University, 2019)
The aim of the study was to develop an algorithm of formation of risk groups among reproductive age women for having children with neural tube defects based on the detection of endogenous and exogenous risk factors and to offer a differentiated approach to fetal NTD prevention. A retrospective analysis of risk factors in women who gave birth to children with NTD (175 women) compared with the control group (60 mothers of children without NTD , congenital malformations and other chromosomal aberrations) and a prospective analysis of the folate cycle metabolic disorders and MTHFR gene polymorphisms C677T and A1298C was carried out. The inclusion criteria for reproductive age women in risk groups for fetal NTD should be regarded as the identification of at least one of the following risk factors: burdened obstetric history on miscarriages and/or prenatal fetal death (OR = 3.4); residence in polluted areas and the using of well water for cooking (OR = 2.7 ); burdened family history of strokes, heart attacks, varicose disease, vessels thromboembolism and thrombosis (OR = 3.04 ); burdened family history of gastrointestinal tract and/or reproductive system cancer (OR 2.9); burdened family history of congenital malformations (OR 3.9); congenital malformations in other children in the family (OR 4.36); maternal age older than 35 years (OR = 2.1) . When planning a pregnancy women from risk group are offered to identify levels of homocysteine and folic acid in the blood serum. Avaliability of hyperhomocysteinemia alone or in combination with low folate levels in the blood at preconception stage can be considered predictive of fetal NTD formation. The presence of hyperhomocysteinemia is the indication for MTHFR polymorphisms identification to determine preventive measures. Definition of risk group for fetal NTD among reproductive age women and detecting changes in folate metabolism,allows to differentiate preventive measures by determining the timing of the beginning of the admission and doses of folic acid and dietary recommendations.